The Socio-Anthropological Analysis of the National Solid Waste Management Program in Bujumbura City - Ngabirano, Emmanuel; Ndih, Jean Nke; Bigumandondera, Patrice; Nsengiyumva, Venerand; Manirambona, Jean Bosco; Ntavuna, Marc Nyamugabo (European Scientific Journal, ESJ, 2025)
Bujumbura city is one of the oldest cities in the Great Lakes Region. It faces challenges related to solid waste management. Despite initiatives implemented by Burundi since 1983, the qualitative research and socio-anthropological analysis show that environmental awareness and education need to be strengthened so as to achieve sustainable solid waste management.